Effects of stress‐shielding on the dynamic viscoelasticity and ordering of the collagen fibers in rabbit Achilles tendon. Issue 11 (6th July 2013) - Ikoma, Kazuya; Kido, Masamitsu; Nagae, Masateru; Ikeda, Takumi; Shirai, Toshiharu; Ueshima, Keiichiro; Arai, Yuji; Oda, Ryo; Fujiwara, Hiroyoshi; Kubo, Toshikazu
Abstract We investigated the effects of stress‐shielding on both viscoelastic properties and microstructure of collagen fibers in the Achilles tendon by proton double‐quantum filtered (1H‐DQF) NMR spectroscopy. The right hind‐limbs of 20 Japanese white rabbits were immobilized for 4 weeks in a cast with the ankle in plantarflexion. Dynamic viscoelasticity of the Achilles tendons was measured using a viscoelastic spectrometer. Proton DQF NMR signals were analyzed to determine the residual dipolar coupling of bound water molecules in the Achilles tendons. Both the dynamic storage modulus (E′) and dynamic loss modulus (E″) decreased significantly in the Achilles tendons of the stress‐shielding group. The results of the 1H‐DQF NMR examination demonstrated significantly reduced residual dipolar coupling in the Achilles tendons of this same group. The disorientation of collagen fibers by stress‐shielding should contribute to degradation of the dynamic storage and loss moduli. The alterations of the collagen fiber orientation that contributed to the function of tendinous tissue can be evaluated by performing an analysis of 1H DQF NMR spectroscopy. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31:1708–1712, 2013